Adenosine A1 Receptor Agonist 2-chloro-N6-cyclopentyladenosine and Hippocampal Excitability During Brain Development in Rats - Fabera, Petr; Parizkova, Martina; Uttl, Libor; Vondrakova, Katerina; Kubova, Hana; Tsenov, Grygoriy; Mares, Pavel (Frontiers in Pharmacology, 2019)
Objective: The adenosinergic system may influence excitability in the brain. Endogenous and exogenous adenosine has anticonvulsant activity presumably by activating A1 receptors. Adenosine A1 receptor agonist 2-chloro-N6-cyclopentyladenosine (CCPA) may thus bolster anticonvulsant effects, but its action and the number of A1 receptors at different developmental stages are not known. Methods: Hippocampal epileptic afterdischarges (ADs) were elicited in 12-, 15-, 18-, 25-, 45-, and 60-day-old rats. Stimulation and recording electrodes were implanted into the dorsal hippocampus. The A1 receptor agonist 2-chloro-N6-cyclopentyladenosine (CCPA, 0.5 or 1 mg/kg) was administered intraperitoneally 10 min before the first stimulation. Control animals were injected with saline. All rats were stimulated with a 2-s series of 1-ms biphasic pulses delivered at 60 Hz with increasing stepwise intensity (0.05–0.6 mA). Each age and dose group contained 9–14 animals. The AD thresholds and durations were evaluated, and the A1 receptors were detected in the hippocampus in 7-, 10-, 12-, 15-, 18-, 21-, 25-, 32-, and 52-day-old rats. Results: Both CCPA doses significantly increased hippocampal AD thresholds in 12-, 15-, 18-, and 60-day-old rats compared to controls. In contrast, the higher dose significantly decreased AD threshold in the 25-day-old rats. The AD durations were significantly shortened in all age groups except for 25-day-old rats where they were significantly prolonged. A1 receptor expression in the hippocampus was highest in 10-day-old rats and subsequently decreased. Significance: The adenosine A1 receptor agonist CCPA exhibited anticonvulsant activity at all developmental stages studied here except for 25-day-old rats. Age-related differences might be due to the development of presynaptic A1 receptors in the hippocampus.